FROM VISUAL CUES TO MUSICAL MNEMONICS: ADAPTATION IN ANGGUK DANCE FOR MUSICIANS WITH VISUAL IMPAIRMENTS - Nurvijayanto, Ribeth; Prakasiwi, Galih; Rahayu, Idhayu Mugia Ningrat Tri (Universitas Gadjah Mada, 2026)
This research investigates the development of creative, effective, and applicable inclusive learning methods in traditional Indonesian music and dance, focusing on individuals with disabilities at Sanggar Sripanglaras in Kulon Progo, Yogyakarta. This study employs a qualitative method with a participant observer and ethnomusicological approach. Data were gathered through a combination of observational studies, interviews, and a thorough analysis of documents related to the practice of teaching music and Angguk dance to students with visual, hearing, speech, and intellectual impairments, as well as those with down syndrome. The results demonstrate that the studio’s pedagogy adheres to a gradual, participatory approach, leveraging auditory senses and musicality to enhance the students’ capabilities. The acquisition of knowladge extends beyond technical aptitudes to include the cultivation of mental resilience and character. The musical aspect is explored using Rahayu Supanggah’s concept of “garap”, while the educational ascpect is analyzed through Bloom’s taxonomy. Sanggar Sripanglaras has emerged as a prominent social and educational institution that fosters inclusivity, promoting cohesion and fostering the growth of self-esteem in children with disabilities throught the mediums of traditional music and dance. These findings can serve as a model for sustainable inclusive arts education that is relevant to the arts education needs of people with disabilities in Indonesia.